UJI FITOKIMIA PADA TUMBUHAN PURUN DANAU (Lepironia articulata) - Hafizh Widhoyo; Kurdiansyah Kurdiansyah; Yuniarti Yuniarti (Universitas Lambung Mangkurat, 2020)
Purun lake (Lepironia articulata) is a plant that belongs to the cyperaceae family and grows in the swamp area. This study aims to determine the content of active chemical compounds in the roots, flowers, and rods purun lake qualitatively through phytochemical tests. This study is expected to provide information about the content of active chemical compounds in the roots, flowers, and stalks of the lake purun which can be used as a basis in its further use as a nutritious plant as a medicine. The sampling of purun lake is done in Kampung Purun Banjarbaru City, while the test is done in Wood Science Laboratory Faculty of Forestry Lambung Mangkurat UniversityBanjarbaru. The method used is phytochemical screening by identifying alkaloid compounds, flavonoids, steroids, triterpenoids, tannins, saponins, and quinones contained within the roots, flowers, and stalks of the lake. Tabulation of data of test result of active chemical compound was analyzed descriptively. The result of phytochemical screening of active chemical compounds contained in the roots, flowers, and stalks of the purun lake shows that their roots contain flavonoids, tannins, and saponins, while the flowers contain alkaloids, flavonoids, tannins and saponins, and the stalks contain alkaloids, steroids, tannins , and saponins.Keywords: Phytochemical screening; purun lake;medicinal herb